CAUSES AND MANAGEMENTS OF HAIR LOSS IN WOMEN - Norshazreen Nazri; I Wayan Sugiritama (Bali Journal of Medical and Health Sciences, 2013)
Alopecia or hair loss is a quite disturbing case. It can occur in both women and men. In women, the most familiar reason for hair loss is telogen effluvium (TE)succeed by female pattern hair loss (FPHL) and chronic telogen effluvium (CTE). Telogen effluvium generally occurs at any age, it is caused by prematurely transition of anagen hairs to telogen hairs. It can be induced by several events such as physiologic or emotional stress or certain drugs. Meanwhile, female pattern hair loss is caused by increasing of 5?-reductase enzymes and androgen receptors in effected scalp. Chronic telogen effluvium is the shedding of telogen hairs that occur over 6 month with idiopathic cause. There are also other causes of hair loss in women such as alopecia areata (AA), trichotillomania, and traction alopecia.TE and CTE are treated by removing the triggering factors. Patients need to be informed and educated that it is self limited and usually resolve with time. For FPHL, the treatment includes minoxidil 2% solution, antiandrogen therapies and hair transplantation. Meanwhile, AA is treated by intralesional corticosteroid injection, psoralen and ultraviolet A (PUVA). In the other hand, women with trichotillomania and traction alopecia need counselling and education to change their behaviours. Keywords: Telogen effluvium, Female pattern hair loss, Chronic telogen effluvium, 5?-reductase enzymes, Androgen receptors